Plexus Brachialis - Arslan, Ayla (Anatomiye Güncel Bakış II, 2024)
Plexus brachialis, son dört servikal spinal sinir ve birinci torakal spinal sinirin ön dallarıyla dördüncü servikal ve ikinci torakal spinal sinirin ön dallarından gelen liflerin birleşmesiyle oluşur. Yedi segmente ait spinal sinirlerin ön dalları birleşerek önce truncus’ları meydana getirir. Truncus’lardan ayrılan dalların birleşmesiyle fasciculus’lar meydana gelir. Son olarak da fasiculus’lardan ayrılan dallar periferik sinirleri meydana getirir. Beşinci ve altıncı servikal spinal sinirlerin ön dalları, dördüncü servikal sinirden gelen dalla birleşerek truncus superior’u, yedinci servikal sinirin ön dalı tek başına truncus medius’u meydana getirir. Sekizinci servikal sinir ile birinci torakal sinirin ön dalı ikinci torakal sinirden gelen bir dal ile birleşerek truncus inferior’u meydana getirir. Truncus superior ve truncus medius’un ön dallarının birleşmesi ile fasciculus lateralis meydana gelir. Truncus inferior’un ön dalı ise fasciculus medialis’i oluşturur. Üç kökün arka dalları fasciculus posterior’u meydana getirir. Bu fasciculuslar a. axillaris’e konumlarına göre adlandırılır. Plexus brachialis’in clavicula’nın üstündeki kısmı pars supraclavicularis olarak adlandırılır ve burada pleksusun kökleri, truncuslar’ı, fasciculus’ların başlangıç bölümleri yer alır. Clavicula’nın altında pars infraclavicularis olarak adlandırılır ve burada fasciculus’ların son bölümleri, uç dalları yer alır. Plexus brachialis boyunda trigonum cervicale posterior’da yer alır. Günümüzde artan trafik kazaları, iş kazaları ve silahlı yaralanmalar nedenleriyle periferik sinir yaralanmalarında da artış görülmektedir. Plexus brachialis doğum, motosiklet, kayak, dağcılık kazaları, kolun bir yerde asılı kalması ve koldan çekilerek sürüklenme ile de zedelenebilir. Erişkinlerde emniyet kemeri, çocuklarda ve askerlerde ağır sırt çantasının uzun kullanımı sonucu plexus brachialis lezyonları gelişebilir. Plexus brachialis anatomisi ve varyasyonlarının bilinmesi boyun, omuz ve aksiller bölgeye yapılacak cerrahi girişimlerde sinirlerin zedelenme oranını düşürür. Plexus brachialis is formed by the union of the last four cervical spinal nerves and the anterior branches of the first thoracic spinal nerve and the fibers from the fourth cervical and second thoracic spinal nerves. The anterior branches of the spinal nerves belonging to the seven segments unite to form the truncus. Fascicules are formed by the union of branches separated from truncus. Finally, the branches leaving the fascicles form the peripheral nerves. The anterior branches of the fifth and sixth cervical spinal nerves combine with the branch from the fourth cervical nerve to form the truncus superior, and the anterior branch of the seventh cervical nerve alone forms the truncus medius. The eighth cervical nerve and the anterior branch of the first thoracic nerve combine with a branch from the second thoracic nerve to form the truncus inferior. The fasciculus lateralis is formed by the union of the anterior branches of the truncus superior and truncus medius. The anterior branch of the truncus inferior forms the fasciculus medialis. The posterior branches of the three roots form the fasciculus posterior. These fascicles are a. The axillaris are named according to their location. The part of the plexus brachialis above the clavicle is called pars supraclavicularis, and here the roots of the plexus, truncus, and the initial parts of the fasciculus are located. Under the clavicle, it is called pars infraclavicularis, and here the last sections and end branches of the fasciculus are located. Plexus brachialis is located in the trigonum cervicale posterior in the neck. Nowadays, there is an increase in peripheral nerve injuries due to increasing traffic accidents, work accidents and gunshot wounds. Plexus brachialis can also be damaged by birth, motorcycle, skiing, mountaineering accidents, hanging the arm in one place, or being dragged by the arm. Plexus brachialis lesions may develop as a result of prolonged use of seat belts in adults and heavy backpacks in children and soldiers. Knowing the anatomy of the plexus brachialis and its variations reduces the rate of nerve damage in surgical interventions to the neck, shoulder and axillary region.